Latin America meets China and India: Prospects and challenges for trade and investment - Osvaldo Rosales; Mikio Kuwayama (CEPAL Review, 2007)
The high growth levels projected for China and India will make these two countries the most important pole of the global economy for the next few years, creating a market of great potential for Latin American and Caribbean exports. These markets had remained largely untapped until recently, with the exception of certain South American primary products. Latin America should strengthen its ties with the two Asian countries, in order to increase production synergies with them. Free trade agreements and trade and investment partnerships should also be established, in order to increase access to both markets and facilitate insertion into Asian production and export chains.